Documentación - G.-Huidobro S., J. Eduardo, (Documento histórico) (ECA: Estudios Centroamericanos, 1971)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 26, No. 274-275, 1971: 575-585.